Firm-level Innovation in Africa: overcoming limits and constraints - (:unkn) unknown (My University, 2016)
This special issue compiles papers from across the African continent, ranging from Tanzania and Ethiopia in the East to Nigeria in the West.11. These papers were selected after a thorough double-blind review process. Two independent reviewers assessed each paper and several of the papers had to undergo multiple review rounds. We are immensely grateful to all the scholars who gave their time and expertise to the review process.View all notesThe six papers included in the collection adopt different but complementary theoretical and methodological approaches. This introductory article proceeds by highlighting some aspects of the innovation landscape in Africa, with particular emphasis on the prevalence of innovation and the distribution of information sources across countries. It then discusses the most important constraints to innovation in Africa and shows how the articles in this compilation advance the related research agenda. Finally, a number of issues on which knowledge remains limited are raised.
Keywords: African Research